{ x + y = 5 ( x + 3 ) 2 + y 2 = 30 {\displaystyle {\begin{cases}x+y=5\\(x+3)^{2}+y^{2}=30\end{cases}}}
{ y = 5 − x ( x + 3 ) 2 + y 2 = 30 {\displaystyle {\begin{cases}y=5-x\\(x+3)^{2}+y^{2}=30\end{cases}}}
( x + 3 ) 2 + ( 5 − x ) 2 = 30 x 2 + 6 x + 9 + 25 − 10 x + x 2 = 30 2 x 2 − 4 x + 4 = 0 x 2 − 2 x + 2 = 0 {\displaystyle {\begin{aligned}(x+3)^{2}+(5-x)^{2}=30\\x^{2}+6x+9+25-10x+x^{2}=30\\2x^{2}-4x+4=0\\x^{2}-2x+2=0\\\end{aligned}}}
דלתא של המשוואה היא שלילית Δ = 4 − 4 ∗ 2 = − 4 {\displaystyle \Delta =4-4*2=-4} ולכן לא ניתן להוציא שורש. במילים אחרות המשוואות זרות.